2021
DOI: 10.3390/ijerph182111512
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Psychological Status and Health Behaviors during the Coronavirus Disease Pandemic in Japanese Community-Dwelling Older Adults

Abstract: The coronavirus disease (COVID-19) continues to be a widespread pandemic. We investigated the relationship between anxiety/stress and health behaviors during the COVID-19 pandemic in homebound Japanese older adults during January and February 2021. We surveyed 1507 community-dwelling, older Japanese adults using a self-administered questionnaire on primary attributes, including family structure, evaluation of psychological anxiety/stress, and health behaviors. Participants were divided into four anxiety/stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…help reduce anxiety. According to Hara et al (2021) [8], health behaviors were significantly associated with anxiety (p <.001).Further, Chayanit Luevanich et al (2020) [24] found that the participants with a good level of health literacy had a very good level of new normal behavior; communication skills for COVID-19 prevention and media and information literacy could explain 52.2% of the participants' new normal behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…help reduce anxiety. According to Hara et al (2021) [8], health behaviors were significantly associated with anxiety (p <.001).Further, Chayanit Luevanich et al (2020) [24] found that the participants with a good level of health literacy had a very good level of new normal behavior; communication skills for COVID-19 prevention and media and information literacy could explain 52.2% of the participants' new normal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Good health behaviors are critical for minimizing stress and anxiety in older adults. Hara et al (2021) also indicated that health behaviors were statistically significantly correlated with anxiety (p<0.01) [8].…”
Section: Introduction 1background and Significance Of The Problemmentioning
confidence: 96%
See 1 more Smart Citation